Effect of the three Enterococcus faecalis strains on apoptosis in MC3T3 cells. (19th October 2018) - Li, Yang; Tong, Zhongchun; Ling, Junqi
Abstract: Objective: Osteoblast apoptosis is critical for the development and repairing of bone destruction in persistent apical periodontitis (PAP). Enterococcus faecalis is considered as a frequently isolated pathogen of PAP. This study aimed to explore the effect of E. faecalis on apoptosis in osteoblastic MC3T3‐E1 cells via an in vitro model. Materials and Methods: MC3T3 cells were incubated with live clinically isolated strains of E. faecalis at a multiplicity of infection (MOI) of 1, 000:1 for 2 hr. Flow cytometry analysis using annexin V‐FITC and PI staining, JC‐1 staining and TUNEL assay were conducted to detect the apoptosis in the infected cells. Western blotting and quantitative real‐time PCR were used to determine the expression of caspase‐3, Bcl‐2 and Bax. Results: The proliferation of the infected cells was inhibited. Decreased mitochondrial membrane potential (ΔΨm) and enhanced DNA fragmentation of the infected cells were observed. The relative expression of Bax and cleavage caspase‐3 was upregulated, and the expression of Bcl‐2 and Bcl‐2/Bax was downregulated in the infected cells. Conclusion: Together, the clinically isolated strains of E. faecalis can induce apoptosis in MC3T3 osteoblasts, which may be attributed to the regulation of interaction between members of the Bcl‐2 family.